2020
DOI: 10.1016/j.petrol.2019.106565
|View full text |Cite
|
Sign up to set email alerts
|

Well control optimization using a two-step surrogate treatment

Abstract: Large numbers of flow simulations are typically required for the determination of optimal well settings. These simulations are often computationally demanding, which poses challenges for the optimizations. In this paper we present a new two-step surrogate treatment (ST) that reduces the computational expense associated with well control optimization. The method is applicable for oil production via waterflood, with well rates optimized at a single control period. The two-step ST entails two separate optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Physics-based approaches can approximate the original reservoir behavior with lower-order equations to reduce the computational cost. However, they have been so far tested on synthetic, box-shaped models only (de Brito and Durlofsky, 2020a;de Brito and Durlofsky, 2020b) and can become unrepresentative in real fields with often complex structures. ML techniques are widely applied within the context of well control optimization (Ahmadi and Bahadori, 2015;Golzari et al, 2015;Chugh et al, 2016;Guo and Reynolds, 2018;Chen et al, 2020;Zhao et al, 2020) and are shown to provide a reasonably accurate, data-driven SM while considering the reservoir simulator as a black box.…”
Section: Introductionmentioning
confidence: 99%
“…Physics-based approaches can approximate the original reservoir behavior with lower-order equations to reduce the computational cost. However, they have been so far tested on synthetic, box-shaped models only (de Brito and Durlofsky, 2020a;de Brito and Durlofsky, 2020b) and can become unrepresentative in real fields with often complex structures. ML techniques are widely applied within the context of well control optimization (Ahmadi and Bahadori, 2015;Golzari et al, 2015;Chugh et al, 2016;Guo and Reynolds, 2018;Chen et al, 2020;Zhao et al, 2020) and are shown to provide a reasonably accurate, data-driven SM while considering the reservoir simulator as a black box.…”
Section: Introductionmentioning
confidence: 99%
“…Ohers [3] have proposed an iterative or nested scheme where the well placement and configuration is optimized in an outer loop and the well controls are optimized in the inner loop, given the well types and locations. Recent improvement to the nested approach [4] apply a two-step process, optimizing well placement assuming certain constraints, and then optimizing well rates. However, this approach assumes simplified physics of 1-D flow.…”
Section: Introductionmentioning
confidence: 99%